Indigenous Chinese fermented dairy products: Microbial diversity, flavour, and health benefits. (December 2022) - Xia, Aonan; Jiang, Yang; Li, Baokun; Wang, Tong; Zhao, Jianxin; Liu, Xiaoming; Chen, Wei
Abstract: China has a long history of producing and consuming fermented dairy products, and these traditional fermented dairy products (TFDP) have made important contributions to social development and human health. A detailed review of their characteristics is crucial to understand the functions of the various microorganisms that shape and define TFDP and the microorganisms' correlations with nutritional value, flavour and texture profile, and health benefits. This review focuses on the basic composition, microbial diversity, flavour profile, and health benefits of Chinese TFDP, and discusses the latest advancements in the understanding of their microbial ecology and flavour profiles. This review also examines the limitations of existing studies on the health benefits of these foods, to encourage the establishment of population-based diet and health databases, as well as randomised controlled trials addressing the mechanisms of health outcomes associated with the consumption of Chinese TFDP.